Role of ECMO in life threatening intoxication - Vivek Gupta; Rajiv Gupta; Gurpreet S. Wander (Egyptian Journal of Critical Care Medicine, 2018)
Abstract Acute severe poisoning may lead to life threatening situation or death due to cardiovascular dysfunction or stunning, arrhythmia or cardiogenic shock. These substances include medications, substances used for addiction, house hold chemicals, industrial, plants and animal or vegetable toxicants. The poison profile varies in different parts of world; drugs with cardiotoxic potential are the common poisoning substances while pesticides and other house hold toxins are common in the other part of the world. Irrespective of the type of the poison, these patients are relatively young and usually healthy. Extracorporeal Life Support (ECLS) has become popular in the management of acute severe intoxication induced cardiogenic shock, arrhythmia or cardiac arrest as bridge therapy. The management of poisoning include further reduction of absorption or enhancing the elimination; antidote administration (if available); and supportive therapies including resuscitation. ECMO helps in maintaining adequate cardiac output and tissue perfusion and enhances the toxic substance metabolism. However most of the available literature is based on case reports, case series and retrospective cohort study. In spite of high mortality with severe poisoning and encouraging outcome with use of ECMO, it is underutilized modality across the world. The available literature shows a favourable outcome with ECMO in severely intoxicated patients with cardiovascular collapse, however, there are no clear guidelines for the time of initiation of ECMO on the basis of clinical, metabolic and echocardiographic parameters. Even prognostication prior to initiation of ECMO is difficult to predict. ELSO (Extracorporeal Life Support Organization) may support the global data collection on acute intoxication requiring ECMO, which may address some of these issues.